Characterization of the microbiome in the infant diapered area: Insights from healthy and damaged skin. Issue 10 (13th October 2020) - Teufel, Amber; Howard, Brian; Hu, Ping; Carr, Andrew N.
Abstract: It has been recognized for nearly a century that human beings are inhabited by a remarkably dense and diverse microbial ecosystem, yet we are only just beginning to understand and appreciate the many roles that these microbes play in human health and development. Establishment of the microbiome begins at birth, but many previous studies on infant skin health have focused on Candida species. Little is known on the full microbial composition across different areas and even less is known on how these communities change during disease/inflammatory states. In this clinical study, infants were recruited during periods of diaper dermatitis (DD) and health to characterize the skin microbiome in these two states. Substantial shifts in the skin microbiome were observed across four sites in the diapered area (genitals, intertriginous, buttocks and perianal), as well as during periods of DD. As DD scores increased, there was a shift in relative abundance that demonstrated higher community percentages of faecal coliforms, such as Enterococcus, and lower percentages of Staphylococcus strains. In high‐rash samples, the predominant Staphylococcus species is S aureus, potentially implicating S aureus as a DD aetiological agent. This study provides new information related to the microbiome on infant skin in the diapered area and provides insights into the role of the microbiome in the development of DD.